USE OF MARKETING RESEARCH TOOLS IN IDENTIFYING THE NEEDS OF PEOPLE WITH LIMITED OPPORTUNITIES - BORYSOVA, Tetiana; OKREPKYI, Rostyslav; DUDAR, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The results of the research carried out by the authors in the course of the project initiated by the public organization «TSWC "Revival of the Nation"» are presented. The analysis of scientific works revealed a lack of research on the current state of needs of people with disabilities at the regional level. The purpose of the article was to identify the needs of consumers of the non-commercial market (women and girls - with limited mobility) in the Ternopil region and to develop recommendations based on the results of the study. The following methods were used: analysis of secondary information; survey using a questionnaire; observation; statistical method; method of comparative analysis; synthesis; generalization; grouping. The following was found: 1. Most often, survey participants turned to institutions/organizations during the last 3 years to issue/reissue pensions for them or their relatives, including on disability, state social assistance to low-income families, assistance from international funds; 2. Among the problems faced by the respondents, the majority of respondents indicated the possibility of using the toilet in the institution, queues, difficulty finding the premises and difficulty moving through the corridors; 3. Every tenth respondent encountered cases of refusal to provide services at the local authority, which were justified by the fact that the local authority does not provide the necessary services to the visitor; 4. Half of the respondents believe that equal access to timely and high-quality medical care is ensured for all persons with disabilities in their community; 5. Accessible transport and expanding the number of services for people with disabilities were among the directions for improving accessibility to services for women/girls with disabilities. The need to intensify the implementation of state documents regarding ensuring the availability of services for persons with special needs at the regional level has been established.